Histological type and marker expression of the primary tumour compared with its local recurrence after breast-conserving therapy for ductal carcinoma in situ - Bijker, N (Nature Publishing Group, 2001)
We have investigated primary ductal carcinomas in situ (DCIS) of the breast and their local recurrences after breast-conserving therapy (BCT) for histological characteristics and marker expression. Patients who were randomized in the EORTC trial 10853 (wide local excision versus excision plus radiotherapy) and who developed a local recurrence were identified. Histology was reviewed for 116 cases; oestrogen and progesterone receptor status, and HER2/ neu and p53 overexpression were assessed for 71 cases. Comparing the primary DCIS and the invasive or non-invasive recurrence, concordant histology was found in 62%, and identical marker expression in 63%. Although 11% of the recurrences developed at a distance from the primary DCIS, nearly all these showed the same histological and immunohistochemical profile. 5 patients developed well-differentiated DCIS or grade I invasive carcinoma after poorly differentiated DCIS. Although these recurrences occurred in the same quadrant as the primary DCIS, they may be considered as second primary tumours. Only 4 patients developed poorly differentiated DCIS or grade III invasive carcinoma after well differentiated DCIS. We conclude that in most cases the primary DCIS and its local recurrence are related histologically or by marker expression, suggesting that local recurrence usually reflects outgrowth of residual DCIS; progression of well differentiated DCIS towards poorly differentiated DCIS or grade III invasive carcinoma is a non-frequent event. © 2001 Cancer Research Campaign http://www.bjcancer.com